2017
DOI: 10.1016/j.trd.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

One-way and round-trip carsharing: A stated preference experiment in Beijing

Abstract: This study examines the factors that influence the use of carsharing systems in Beijing, as well as the potential for carsharing systems that integrate electric vehicles. Investigated variables include weather, air quality, price, vehicle attributes and "status" indicators. Additionally, we explore how the impacts of these factors differ when carsharing is utilized for one-way trips as compared with round-trips. The study relies on a pen-and-paper survey (1,010 completed survey forms with 2,023 reported trips)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 42 publications
(36 reference statements)
5
27
1
Order By: Relevance
“…Unlike previous studies in San Francisco [23], Basel, Switzerland [26], Shanghai [33], and Beijing [34], women in this study and studies in Peshawar, Pakistan [49], and Salerno, Italy [25] are found more willing to use carsharing, probably because most commuters in the sample come from families with cars, where men are often main car users. In this case, women may prefer to use carsharing if they want to use a motorized private commute mode.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies in San Francisco [23], Basel, Switzerland [26], Shanghai [33], and Beijing [34], women in this study and studies in Peshawar, Pakistan [49], and Salerno, Italy [25] are found more willing to use carsharing, probably because most commuters in the sample come from families with cars, where men are often main car users. In this case, women may prefer to use carsharing if they want to use a motorized private commute mode.…”
contrasting
confidence: 99%
“…The result of Martin et al's study [11] showed that the average number of vehicles per household of carsharing members in North America fell from 0.47 of people choosing EV carsharing were male, aged between 18 and 30 years old, and usually took subway and bus as the daily travel modes. In order to explore the market potential of carsharing system in Beijing, Yoon and Chery [34] developed a binary logit model on whether they would like to use carsharing in one-way and round-trip travel based on RP and SP survey data. The results showed that age, income, gender, gated apartment residence, car ownership, comfort index of subways users, shelter mode, and so on were important influential factors.…”
Section: Introductionmentioning
confidence: 99%
“…Electric car sharing can provide economic and environmental benefits by reducing environmental pollution [25][26][27][28][29][30]. A stated preference experiment regarding one-way and round-trip car sharing systems was conducted in Beijing to examine which factors influence the use of car sharing systems [31]. The results showed that people who are non-car-owners preferred using car sharing for round-trips.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the EVs' purchase price is higher than that of gasoline or diesel vehicles, other variable costs, like fuel and maintenance, and when coupled with purchase subsidies, the registration with incentives, insurance, maintenance, repairs, and the energy price of EVs are lower than those of CVs [13,14].…”
Section: Electric Vehiclesmentioning
confidence: 99%
“…The constraint given by Equation (14) enforces that the minimum estimated life for k-type vehicles in year i should be longer than the break-even year, assuring that the increased capital cost of EVs are recovered in fuel and maintenance savings before resale.…”
Section: Fleet Composition Optimizationmentioning
confidence: 99%